Optimal jersey retirement in the National Basketball Association. (2nd April 2020) - Mildebrath, David; Knight, Wendy; Schaefer, Andrew
Abstract: One of the highest honors an individual player in the National Basketball Association (NBA) can receive is to have their jersey number retired by a franchise. Players selected for jersey retirement are often chosen carefully, in part because each franchise has only a finite number of jerseys available for retirement. In this work, we present a method to optimize the selection of players to honor with jersey retirement. We first present a Markov Decision Process (MDP) to model the jersey retirement decisions of a given franchise. We then embed this MDP into a nonlinear regression model, which we solve approximately using a modified support vector machine. Our results indicate that most NBA franchises behave approximately in accordance with our optimality criteria. We also use our model to suggest optimal retirement decisions for several NBA franchises.